The influence of arms action on the kinematics of grab start in swimming - Skyriene, V.; Satkunskiene, D. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2002)
The purpose of this study was to determine the influence of arms action on the kinematics of grab start in swimming. Material and Methods. Fourteen Lithuanian top-level swimmers were included in the study. Each swimmer performed five starts, with a rest period longer than 5 minutes. The starts were analysed with one video camera filming the swimmers in the sagittal plane; 50 pictures per second were recorded. Using SIMI Motion 2D still mode software selected temporal and kinematics parameters of starts were obtained; fifty-eight starts were analysed. Horizontal position of the hip joint, angle between the trunk and horizontal axis, between arms and horizontal axis, between the tight and shank were estimated at the start position, at the start of push-off, at the instant of take-off and entry. Takeoff and entry orientation were defined as the angle of the trunk segment relative to the horizontal. Flight distance was defined as the horizontal distance the hip joint travelled from takeoff to water entry. Start distance was defined as the horizontal distance between the block front edge and the point of contact with the water at water entry. Relative start distance was calculated by dividing start distance by the full body length. Each start as recorded on video camera was broken down into five phases: reaction, preflexion, push-off, flight and entry. Additional duration of hands contact and block time was recorded. The STATISTICA (v 6.0) package was used for statistical analysis of the data. Correlation matrices were calculated between selected variables, using either 0.05 or 0.01 error levels for statistical significance. Results. The correlation data showed significant and high correlation values between duration of hands contact the starting block platform and preflexion time (r = 0.87, p<0.001), and block time (r = 0.86, p< 0.001). The duration of preflexion phase correlated with the angle of the trunk segment relative to the horizontal axis at the instant of take-off (r = -0.42, p< 0.001). The angle of the trunk at the instant of take-off correlated with the time of flight (r = 0.55 p<0.001). There was strong relationship between flight duration and relative start distance (r = 0.76, p< 0.001). Also significant correlation was marked between the angle of the trunk relative to the horizontal axis as well as the angle of the arms.